Whole-transcriptome sequencing identifies key differentially expressed circRNAs/lncRNAs/miRNAs/mRNAs and linked ceRNA networks in adult degenerative scoliosis - Shi, Xin; Li, Panpan; Wu, Xiang; Shu, Jun (Frontiers in Molecular Neuroscience, 2023)
Background Adult degenerative scoliosis (ADS) is forecast to be a prevalent disabling condition in an aging society. Universally, its pathogenesis is perceived as intervertebral disc degeneration (IDD), however, a thought-provoking issue is why precisely a subset of patients with disc degeneration develop ADS. Exploring the diversities between common IDD and ADS would contribute to unraveling the etiological mechanisms of ADS. Therefore, we aimed to integrate the circRNA, lncRNA, miRNA, and mRNA expression profiles from normal adults (Normal), patients with lumbar disc herniation (LDH), and ADS by whole transcriptome sequencing, which identifies critical functional ncRNA and ceRNA networks and crosstalk between the various transcripts. Methods The fresh whole blood samples (n = 3/group) were collected from ADS patients, LDH patients, and healthy volunteers (Normal group), which were examined for mRNA, miRNA, lncRNA, and circRNA expression and screened for differentially expressed (DE) ncRNAs. Then, Gene Ontology (GO) and KEGG analyses were performed for gene annotation and enrichment pathways on the DE RNAs, which were constructed as a lncRNA-miRNA-mRNA network. Eventually, DE RNAs were validated by qRT-PCR targeting disc nucleus pulposus (NP) tissue in ADS and LDH group (n = 10/group). Results Compared to the LDH group, we identified 3322 DE mRNAs, 221 DE lncRNAs, 20 DE miRNAs, and 15 DE circRNAs in the ADS. In contrast to Normal, 21 miRNAs and 19 circRNAs were differentially expressed in the ADS. The expression of multiple differentially expressed ncRNAs was confirmed by qRT-PCR analysis to be consistent with the sequencing results. In addition, GO, and KEGG analysis demonstrated that most DE mRNAs and ncRNAs target genes are involved in various biological processes, including Endocytosis, Apoptosis, Rap1 signaling pathway, Notch signaling pathway, and others. The constructed lncRNA-miRNA-mRNA co-expression network was primarily related to angiogenesis and regulation. Conclusion By focusing on comparing asymmetric and symmetric disc degeneration, whole-transcriptome sequencing and bioinformatics analysis systematically screened for key ncRNAs in the development of ADS, which provided an abundance of valuable candidates for the elucidation of regulatory mechanisms. The DE ncRNAs and the lncRNA-miRNA-mRNA network are intrinsically involved in the regulation of mediator and angiogenesis, which may contribute to the insight into the pathogenesis of ADS.